Reactions of Nitroarenes with Corey–Chaykovsky Reagents - Antoniak, Damian; Barbasiewicz, Michał (Synlett, 2022)
Electrophilic and nucleophilic substitutions of aromatic substrates share common mechanistic pathways. In both scenarios reacting species attack rings at the unsubstituted (C–H) positions, giving cationic Wheland intermediates or anionic Meisenheimer complexes. However, the following step of rearomatization breaks the intrinsic symmetry, due to different leaving group ability of proton and hydride anion, respectively. In effect, electron-deficient arenes are prone to transformations unparalleled in electrophilic chemistry. In our article, we present transformations of anionic σH-adducts, formed between nitroarenes and carbanions of the Corey–Chaykovsky reagents. Depending on structure of the substrates and reaction conditions, the intermediates undergo cyclization to cyclopropanes (norcaradienes) or base-induced elimination to the alkylated products. Mechanistic studies reveal that order of the carbanions controls competition between the processes, due to steric hindrance developing at the β-elimination step.1 Introduction2 Cyclopropanation of Nitronaphthalenes3 Alkylation of Nitropyridines4 Mechanistic Studies5 Summary and Outlook
Keywords: nitroarenes; sulfones; selenones; sulfonium salts; cyclopropanation; alkylation; carbanions; Meisenheimer complex